An analytical approach for allocation and sizing of distributed generations in radial distribution network. (2nd February 2017) - Kayal, Partha; Chanda, Sayonsom; Chanda, Chandan Kumar
Summary: This article presents a simple model to identify the proper location and size of distributed generations (DGs) in radial distribution networks. The proposed model is a combination of a 2‐stage framework that determines a suitable location for DG and appropriate size at obtained location. An index is formulated that combines aspects of the real power losses in the network and the voltage stability condition of the network. The index is defined as the DG selection index, and it is used to determine the proper bus location for the DG. On the basis of a DG sizing formula presented in the article, the optimal generation capacity of a DG unit is determined. The proposed methodology is tested on 12‐bus, 33‐bus, and 69‐bus radial distribution network models that consider different operational power factor operation modes of DGs. The simulation results are compared with existing analytical approaches to demonstrate the effectiveness of the proposed methodology in radial network systems.